Systemic and heart autonomous effects of sphingosine Δ4 desaturase deficiency in lipotoxic cardiac pathophysiology - Stanley M. Walls; Dale A. Chatfield; Karen Ocorr; Greg L. Harris; Rolf Bodmer (The Company of Biologists, 2020)
Lipotoxic cardiomyopathy (LCM) is characterized by cardiac steatosis, including the accumulation of fatty acids, triglycerides and ceramides. Model systems have shown the inhibition of ceramide biosynthesis to antagonize obesity and improve insulin sensitivity. Sphingosine Δ4 desaturase (encoded by ifc in Drosophila melanogaster) enzymatically converts dihydroceramide into ceramide. Here, we examine ifc mutants to study the effects of desaturase deficiency on cardiac function in Drosophila. Interestingly, ifc mutants exhibited classic hallmarks of LCM: cardiac chamber dilation, contractile defects and loss of fractional shortening. This outcome was phenocopied in global ifc RNAi-mediated knockdown flies. Surprisingly, cardiac-specific ifc knockdown flies exhibited cardiac chamber restriction with no contractile defects, suggesting heart autonomous and systemic roles for ifc activity in cardiac function. Next, we demonstrated that ifc mutants exhibit suppressed Sphingosine kinase 1 (Sk1) expression. Ectopic overexpression of Sk1 was sufficient to prevent cardiac chamber dilation and loss of fractional shortening in ifc mutants. Partial rescue was also observed with cardiac- and fat-body-specific Sk1 overexpression. Finally, we showed that cardiac-specific expression of Drosophila inhibitor of apoptosis (dIAP) also prevented cardiac dysfunction in ifc mutants, suggesting a role for caspase activity in the observed cardiac pathology. Collectively, we show that spatial regulation of sphingosine Δ4 desaturase activity differentially affects cardiac function in heart autonomous and systemic mechanisms through tissue interplay.